Gender dynamics in the South African apparel value chain: a case study on the Western Cape province - Vika, Lutho (School of Economics, 2017)
Since the early 2000s, South Africa's once thriving sector started to whither due to a combination of domestic and international factors. The result was a sharp decline in manufacturing output, low productivity levels, factory closures and massive job losses across the sector. The blow to the industry was exasperated by the surge of cheap imports, both legal and illegal, primarily coming from China. The poor performance and consequent contraction of the industry had a profound impact on the predominately female workers. In recent years, however, the clothing industry has started to stabilise and is beginning to show positive trends in terms of performance and competitiveness. This paper therefore examines whether female workers have gained from the changes that have taken place in the industry, looking specifically at the Western Cape region. It finds that although the Western Cape clothing industry was the most severely hit by the challenges of global competition, it is now doing relatively well. Furthermore, it argues that the sector is upgrading and providing increased opportunities for women in terms of employment and skills development. This can be attributed to the changes in policy approach by government as well as new and improved production methodologies that are being adopted by firms. Moreover, it argues that the Cape Clothing and Textiles Cluster (CCTC) has played a critical role in driving these processes in the industry primarily through high level trainings and the exposure of executives to the latest industry developments, both nationally and internationally.